Boom! Zoom! - Judith Bauer Stamper (New York, United States Random House Disney, 1998)
In an easy-to-read story using phonics, Ray's trip into space focuses on word families, that is, words that rhyme and contain the same spelling pattern, and skill-building phonics activities by educator Wiley Blevins are included. Original.
Keywords: Level Readers -- Level Readers